Comprehensive Tools to Prevent Stunting Risks (CTP Stunting Risks) in South Kalimantan - Firdaus, Syamsul; Prayogi, Bisepta; Marlinda, Evy; Setyowati, Anggi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Stunting is a condition of chronic malnutrition in children under five. Indonesia is above the World Health Organization (WHO) standard of 20% (Riskesdas, 2018). Data from SSGI South Kalimantan Province in (2021) the prevalence of stunting is 30%, in (2022) the prevalence is 24.6% while the National National Target in (2023) is 14%. The purpose of the study was to produce a risk assessment instrument tool Comprehensive Tools to Prevent Stunting Risk (CTP Stunting Risks) and the relationship between factors that cause stunting. The research design of the assessment instrument through testing the factors that cause stunting is then explored with FGDs to perfect the CTP Stunting Risk instrument product. The total sample of 101 families. Based on the results, There is a relationship between stunting cases and the domain of maternal care, childcare and knowledge level with P Value = 0.000 while the family domestic factor is stated to have no relationship with P Value = 0.708. The instrument used needs to be modified and additional indicators based on the results of FGDs and the expansion of indicators of domestic family factors and the need for in-depth interviews with experts on stunting from various scientific disciplines and expert review of language.